2020
DOI: 10.1111/jocd.13761
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of scar hyperplasia in the skin by conotoxin: A prospective review

Abstract: Scars are often considered to be skin problems that affect beauty. The tension acting on the edge of the wound is the main factor causing the scar hyperplasia. At present, the clinical use of botulinum toxin A (BTX-A) around the wound to cause transient muscle paralysis reduce the muscle movement around the wound and wound tension to prevent scar hyperplasia during wound healing. But the use of BTX-A to prevent scarring requires the use of a syringe. The syringe can cause trauma and pain when How to cite this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…For example, external application of silicone gel, injection of botulinum toxin and lattice laser therapy can reduce scar formation. [4][5][6] However, all the above methods are used to intervene the scar formation process after surgery. In the suture process of facial trauma surgery, as the earliest treatment measure of facial trauma, cosmetic suture technology has the most direct influence on the scar formation after surgery.…”
Section: What This Paper Addsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, external application of silicone gel, injection of botulinum toxin and lattice laser therapy can reduce scar formation. [4][5][6] However, all the above methods are used to intervene the scar formation process after surgery. In the suture process of facial trauma surgery, as the earliest treatment measure of facial trauma, cosmetic suture technology has the most direct influence on the scar formation after surgery.…”
Section: What This Paper Addsmentioning
confidence: 99%
“…At present, there are many methods for scar prevention and treatment. For example, external application of silicone gel, injection of botulinum toxin and lattice laser therapy can reduce scar formation 4–6 . However, all the above methods are used to intervene the scar formation process after surgery.…”
mentioning
confidence: 99%
“… 7 Studies have also shown that the application of a skin wound tension reduction device (SWTRD) on the postoperative incision inhibits the growth of scars. 8 …”
Section: Introductionmentioning
confidence: 99%